Adoção Post Mortem: análise jurídica e seus impactos no direito sucessório brasileiro - (:unkn) unknown (Universidade Federal do Pampa, 2025)
Adoption is a legal institution that legally establishes the bond of filiation between people without a biological relationship, guaranteeing the adopted child the same rights and duties as a biological child. In the case of post-mortem adoption, this bond is recognized even after the death of the adopter, with the aim of ensuring the rights of the adoptee and preserving the unequivocal manifestation of the deceased's will. In this sense, this Final Project aims to study post-mortem adoption in the context of Brazilian Inheritance Law, examining its legal foundations and exploring its social and emotional dimensions. Given the conflicts surrounding the legal recognition of socio-affective bonds within Brazilian Inheritance Law, the research questions how post-mortem adoption affects inheritance and the division of assets. The initial hypothesis is that this type of adoption, despite being legally permitted in Brazil under certain circumstances, may generate uncertainties regarding Inheritance Law. In this sense, the possibility of a property dispute regarding equal rights with biological and adoptive heirs in conventional processes is evident. In light of this, the divergence in case law poses a problem for national legal certainty. Specifically, the aim is to determine that post-mortem adoption, although it plays an essential role in guaranteeing socio-affective bonds and preserving human dignity, requires caution to avoid legal uncertainty, especially regarding inheritance law. Therefore, this study explores the concept and the legal conditions for post-mortem adoption to be recognized in Brazil, in order to understand how it can influence the right to inheritance and the adopted child's participation in the division of the adoptee's assets. Concurrently, the research analyzes Brazilian court decisions, highlighting the interpretation of inheritance rights arising from this institution. In order to achieve the proposed objectives, this exploratory work, of a basic nature and qualitative approach, employs the hypothetical-deductive scientific method, as well as the procedural technique of indirect bibliographic and documentary research.The relevance of this study lies in the urgent need to promote greater legal certainty and predictability in the structuring of family ties within the inheritance process, in line with contemporary transformations in affective relationships and the evolution of family concepts. Thus, the work contributes to understanding the challenges and impacts of post-mortem adoption in Brazil, as well as to building a broader debate about the need for harmonization between the formal and affective aspects of Inheritance Law.
Post-Mortem Adoption: Legal Analysis and its Impacts on Brazilian Inheritance Law
Keywords: Adoção Post Mortem; Direito Sucessório; Direito; Post-Mortem Adoption; Inheritance Law; Right; CIENCIAS SOCIAIS APLICADAS